Commentary: What Education Can Learn From the Arts (LEARNing Landscapes, 2008)
The arts have typically been regarded as non-cognitive activities that are often thought to be more ornamental than useful. This paper examines prevalent assumptions about the arts and identifies forms of thinking that the arts promote. It is argued that far from being merely decorative, the arts stimulate, refine, and convey meanings that cannot be expressed in any other form of representation. The recognition of the demands and the contributions that the arts make is of fundamental importance in justifying the place of the arts in our schools, that is, as being central, rather than peripheral educational accomplishments. This paper identifies a number of the forms of thinking that the arts promote as a basis for building a case for their presence in our schools by regarding them as being substantially more than of marginal importance.
Keywords: arts; education; school; non-cognitive